Shaking table test of pounding tuned mass damper (PTMD) on a frame structure under earthquake excitation - Lin, W.; Wang, Q.; Li, Jun; Chen, S.; Qi, A. (2017)
A pounding tuned mass damper (PTMD) can be considered as a passive device, which combines the merits of a traditional tuned mass damper (TMD) and a collision damper. A recent analytical study by the authors demonstrated that the PTMD base on the energy dissipation during impact is able to achieve better control effectiveness over the traditional TMD. In this paper, a PTMD prototype is manufactured and applied for seismic response reduction to examine its efficacy. A series of shaking table tests is conducted in a three-story building frame model under single-dimensional and two-dimensional broadband earthquake excitations with different excitation intensities. The ability of the PTMD to reduce the structural responses is experimentally invest igated. The results show that the traditional TMD is sensitive to input excitations, while the PTMD mostly has improved control performance over the TMD to remarkably reduce both the peak and root-mean-square (RMS) structural responses under single-dimensional earthquake excitation. Unlike the TMD, the PTMD is found to have the merit of maintaining a stable performance when subjected to different earthquake loadings. In addition, it is also indicated that the performance of the PTMD can be enhanced by adjusting the initial gap value, and the control effectiveness improves with the increasing excitation intensity. Under two-dimensional earthquake inputs, the PTMD controls remain outperform the TMD controls; however, the oscillation of the added mass is observed during the test, which may induce torsional vibration modes of the structure, and hence, result in poor control performance especially after a strong earthquake period.